2009
DOI: 10.1111/j.1475-4932.2009.00565.x
|View full text |Cite
|
Sign up to set email alerts
|

Poverty, Deprivation and Consistent Poverty*

Abstract: Controversy over the setting of poverty lines and its narrow focus on income has undermined the influence of poverty research on policy. The deprivation approach overcomes these limitations by identifying deprivation as an inability to afford items that receive majority support for being essential. This paper estimates the incidence of deprivation and compares the results with those produced using a conventional poverty framework. The results confirm overseas findings by showing that the groups most deprived d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 22 publications
2
45
0
2
Order By: Relevance
“…First it highlights the fact that given the social and contextual nature of poverty rigid application of over simplified and standardized lists of identification criteria are not the way to go. Poverty is best identified by a composite of variables rather than one or a few simple (monetary) variables [8,30,31]. Our study revealed that with regard to material indicators of poverty, the range of indicators covered the themes of employment, ability to put and keep children in school, food availability and consumption, physical appearance, housing conditions, asset ownership, and health seeking behavior.…”
Section: Discussionmentioning
confidence: 98%
“…First it highlights the fact that given the social and contextual nature of poverty rigid application of over simplified and standardized lists of identification criteria are not the way to go. Poverty is best identified by a composite of variables rather than one or a few simple (monetary) variables [8,30,31]. Our study revealed that with regard to material indicators of poverty, the range of indicators covered the themes of employment, ability to put and keep children in school, food availability and consumption, physical appearance, housing conditions, asset ownership, and health seeking behavior.…”
Section: Discussionmentioning
confidence: 98%
“…Harding et al 2001a). Other authors have also undertaken studies to expand the use of income alone as a measure of poverty (see for example, Saunders and Naidoo 2009;Saunders et al 2007b;Saunders 1998b;Social Inclusion Unit 2009b); however none have adopted a multidimensional poverty approach. Due to the perception of the need for a new multidimensional measure of poverty to be developed specifically for Australia, the Freedom Poverty Measure was constructed.…”
Section: Development Of the Freedom Poverty Measurementioning
confidence: 98%
“…That is, they have endeavoured to measure and incorporate the individual's utility function through an assessment of whether purchase of the item was based on its affordability or its desirability to the particular respondent (Saunders 2004). Those who did not possess and could not afford items that are viewed as essential by the majority of respondents are then identified as economically deprived (Nolan & Whelan 1996;Saunders & Naidoo 2009). Research by Saunders has shown that living conditions captured by these measures are negatively and significantly associated with social wellbeing (Saunders & Zhu 2009).…”
Section: Economic Deprivationmentioning
confidence: 99%
“…We determined that a 25 per cent cut-off would be applied and those items where 75 per cent or more of respondents indicated the items were important were retained. Since the selection of such a cut-off point is inevitably somewhat arbitrary and different criteria can lead to different results (for example, Saunders & Naidoo, 2009), the list of selected items was thoroughly screened for conceptual consistency and generalisability to the entire population. Literature findings and conceptual arguments were used to further refine the set of items included in the index.…”
Section: Dependent Variable -Social Wellbeing Indexmentioning
confidence: 99%
See 1 more Smart Citation